Alpha 1-antitrypsin screening of 18-year-old men. - Sveger, T (1979)
In 11 128 apparently healthy 18-year-old men screened for alpha 1-antitrypsin deficiency (AATD) 44 had an alpha 1-antitrypsin (AAT) level of 50% or less of the transferrin reference. In 42 of the 44 the Pi types were: five Pi Z, 10 Pi SZ, three Pi MZ, one presumptive Pi M-, one Pi FM, and 22 Pi M. Probably all Pi Z and most of the Pi SZ subjects were identified. The transferrin reference, however, is probably less reliable for the study of this age group, and alpha 1-antichymotrypsin may provide a more valid reference for the AAT screening procedure. In the clinical investigation the additive risk factor of smoking was discovered in eight of 15 individuals with AATD Pi Z or Pi SZ. We believe screening for Pi Z and probably also Pi SZ AATD should be done before young people start smoking or train for jobs in polluted environments.